Reduksi Dimensi Saluran Drainase Akibat Keberadaan Sumur Resapan Pada Jaringan Drainase Maguwoharjo – Wedomartani, Sleman, Yogyakarta - Sanidhya Nika Purnomo (Jenderal Soedirman University, 2013)
Land use in development area has to be followed by an integrated management of drainage environtment. The concept of drainage design that quickly remove the water from the area only able to reduce the flood, but unable to preserve groundwater. It is necessary to concept the drainage design in environtment perception as an effort to preserve groundwater. One of the effort to handling the drainage in environtment perception is the use of recharge well adjacent to the drainage channel. The result of this research showed that the run off discharge prior to recharge wells can reach 8 m3/s on residential area, and in average 3 m3/s on wetland and upland area. After the recharge well, the run off discharge capable reduce in average 30%, the drainage channel on residential area can reduce in 50%, and in average 30% on wetland and upland area.